Deferasirox, an Iron-Chelating Agent, Improves Testicular Morphometric and Sperm Functional Parameters in a Rat Model of Varicocele. (9th April 2021) - Rahmani, M.; Tavalaee, M.; Hosseini, M.; Eskandari, A.; Shaygannia, E.; Sadeghi, N.; Nazem, M. N.; Gharagozloo, P.; Drevet, J. R.; Nasr-Esfahani, M. H.
Abstract : Varicocele is characterized by testicular dysfunction that originates from hyperthermia and hypoxia, leading to defects in testicular tissue and altered spermatozoa structure and function. The varicocele testis is characterized by the presence of intracellular iron deposits that contribute to the associated oxidative stress. Therefore, we tested the hypothesis that administration of an iron-chelating agent, such as deferasirox (DFX), could potentially mitigate the consequences of varicocele on testicular tissue and spermatozoa. Using a well-established rat model of varicocele (VCL), we show that treatment with DFX partially improved the structure and function of the testis and spermatozoa. In particular, sperm motility was markedly restored whereas abnormal sperm morphology was only partially improved. No significant improvement in sperm count was observed that could be associated with the proapoptotic response observed following iron chelation treatment. No reduction in oxidative damage to spermatozoa was observed since lipid peroxidation and DNA integrity were not modified. This was suggested to be a result of increased oxidative stress. Finally, we also saw no indication of attenuation of the endoplasmic reticulum/unfolded protein (ER/UPR) stress response that we recently found associated with the VCL testis in rats.